POLITIK KEBIJAKAN PANGAN BERBASIS MAQASHID SYARIAH DI PAPUA BARAT DAYA: INTEGRASI PERAN PEREMPUAN DAN MASLAHAH PUBLIK - Etik Siswatiningrum; Nurinaya Nurinaya; Adi Randi M Rajab (JOSH: Journal of Sharia, 2026)
This article examines food policy politics in Southwest Papua Province from the perspective of Maqashid Sharia by focusing on policy orientation toward local food development and women's empowerment as integral components of promoting public welfare (maslahah ammah). As Indonesia's newest autonomous province, Southwest Papua continues to face a high dependence on food supplies from other regions, limited distribution infrastructure, and the underutilization of local food resources such as sago, taro, tubers, and marine products. These conditions indicate that the current political orientation of food policy has not fully supported regional food self-reliance or the protection of local economic actors, particularly Mama-Mama Papua, who play a strategic role in the local food economy. This study aims to analyze how the political orientation of regional food policy can be understood through the perspective of Maqashid Sharia. The research employs a qualitative method using normative juridical and public policy approaches. Data were collected through a literature review of laws and regulations, government policy documents, statistical data, and relevant scholarly literature, and were analyzed descriptively using the Maqashid Sharia framework. The findings reveal that food policy politics in Southwest Papua remains primarily oriented toward securing food supply, while strengthening local food systems, protecting the economic interests of Mama-Mama Papua, and expanding equitable market access have yet to become policy priorities. From the perspective of Maqashid Sharia, this policy orientation has not fully reflected the principles of hifzh al-nafs (the protection of life) and hifzh al-mal (the protection of wealth). The novelty of this study lies in the development of a Maqashid Sharia-based analytical framework for food policy politics that integrates support for local food and women's empowerment as indicators of maslahah ammah. These findings enrich the literature on food policy politics while providing a normative foundation for designing more inclusive, equitable, and regionally oriented food sovereignty policies